Home Price Beliefs in Australia - Windsor, Callan; La Cava, Gianni; Hansen, James (Sydney, 2014)
We document some new stylised facts about how Australian homeowners value their homes using household panel data and unit-record data on home sale prices. We find that homeowners' price beliefs are unbiased at the postcode level, on average, although there is considerable dispersion in the difference between beliefs and prices across postcodes. Household characteristics, such as age and tenure, and the regional unemployment rate are correlated with differences between beliefs and prices. We also find evidence that the difference between beliefs and prices has explanatory power for average household consumption, leverage and portfolio decisions after controlling for the market-inferred value of the home. These facts provide empirical evidence to support recent literature on the importance of belief formation for household decision-making.
Research Discussion Paper
Research Discussion Papers
Keywords: Housing; Beliefs and Values; Housing -- Intentions; Housing, communities and neighbourhoods; Identity; Beliefs and Values; Housing; Intentions; Identity; Housing, communities and neighbourhoods